(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the efficacy and safety of misoprostol administration in medical termination of pregnancy using FIGO protocol Study Design: Prospective descriptive study Place and Duration of study: The study was conducted at the Department of Obstet & Gynae, Fauji Foundation Hospital, Rawalpindi from Jan.2016 to June.2017. Materials and Methods: 73 patients were recruited in the study using non probability consecutive sampling technique. Patients with incomplete miscarriages, missed miscarriages up to 24 weeks and induced miscarriages due to fetal anomaly, anhydramnios, chorioamnionitis, intrauterine fetal demise and medical problems were included in the study. Patients fulfilling the selection criteria were admitted in the hospital. After detailed history and examination, baseline investigations and clotting profile were sent. Written informed consent was taken. Misoprostol administration was done according to the FIGO protocol. The efficacy was determined by successful expulsion of products of conception without surgical intervention. Safety profile was determined by occurrence of severe haemorrhage requiring blood transfusion, infection, retained placenta, uterine rupture. Results: The mean age of study population was 38years +- 5years. 38% of the patients were between 36 to 40 years of age.73%of the patients were multiparous. 17.8% of the patients were with history of prior caesarean section. First trimester missed miscarriage was the most common indication of termination of pregnancy. . The overall success rate was found to be 97.59% with no adverse side effects. Conclusion: FIGO protocol for Misoprostol administration is an effective and safe option for medical termination of pregnancy.